Assessment of the Emerging Threat Posed by Perfluoroalkyl and Polyfluoroalkyl Substances to Male Reproduction in Humans - Calvert, Leah; Green, Mark P.; De Iuliis, Geoffry N.; Dun, Matthew D.; Turner, Brett D.; Clarke, Bradley O.; Eamens, Andrew L.; Roman, Shaun D.; Nixon, Brett (Frontiers in Endocrinology, 2022)
Per-fluoroalkyl and polyfluoroalkyl substances (PFAS) are a diverse group of synthetic fluorinated chemicals used widely in industry and consumer products. Due to their extensive use and chemical stability, PFAS are ubiquitous environmental contaminants and as such, form an emerging risk factor for male reproductive health. The long half-lives of PFAS is of particular concern as the propensity to accumulate in biological systems enhance the time taken for excretion, taking years in many cases. Accordingly, there is mounting evidence supporting a negative association between PFAS exposure and an array of human health conditions. However, inconsistencies among epidemiological and experimental findings have hindered the ability to definitively link causality to specific PFAS exposure. This situation highlights the requirement for further investigation and the identification of reliable biological models that can inform the risks for general health, allowing sensitive assessment of the spectrum of effects of PFAS exposure on humans. Here, we review the literature on the biological effects of PFAS exposure, with a specific focus on male reproduction, owing to its utility as a sentinel marker of general health. Indeed, the demise of male fertility is now known to signal the onset of a range of co-morbidities such as coronary, inflammatory, and metabolic diseases, conditions of increased alarm due to their demonstrated transgenerational consequences. It follows that some of the strongest adverse associations have been established between PFAS exposure and the incidence of testicular dysfunction, including pathologies such as testicular cancer and a reduction in semen quality. Here, we consider the mechanisms that render the male reproductive tract vulnerable to PFAS mediated damage, as well as discuss novel remediation strategies to mitigate the negative impact of PFAS contamination and/or to ameliorate the PFAS load of exposed individuals.